2000
DOI: 10.1128/cdli.7.5.739-744.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Serologic Tests for Diagnosis of Acute Infections by Chlamydia pneumoniae

Abstract: Serology is often used to diagnose acute infections by Chlamydia pneumoniae. In this study paired sera from patients with acute respiratory tract infection during an epidemic of C. pneumoniae infections were examined by five different antibody tests. These tests were the complement fixation (CF) test, the microimmunofluorescence (MIF) test, a recombinant enzyme immunoassay (rEIA) (Medac) based on a recombinant lipopolysaccharide of chlamydia and measuring antibodies to a common chlamydial antigen, and two test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 23 publications
3
68
0
3
Order By: Relevance
“…Several other studies have also shown that high anti-C. pneumoniae-specific IgG titers are common in healthy individuals (24,33,34,38). For the detection of an increase in the IgG titer, analysis of paired serum specimens in the same test run is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have also shown that high anti-C. pneumoniae-specific IgG titers are common in healthy individuals (24,33,34,38). For the detection of an increase in the IgG titer, analysis of paired serum specimens in the same test run is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared five serological tests for the diagnosis of acute infections caused by C. pneumoniae. The MIF and EIA from Labsystems, as well as the SeroCP ELISA and the rELISA, were included in the evaluation (38). Compared to the results of MIF, the specificities and sensitivities of the Labsystems EIA, the SeroCP ELISA, and the rELISA ranged from 89 to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…C. trachomatis-and C. pneumoniaespecific IgG antibodies were measured by the microimmunofluorescence method, which is considered a gold standard of chlamydial serology (31) with specificity estimated at 83% to 89% and sensitivity at 79% to 88% (32,33). Elementary bodies of pooled serovars BED (B-group), CJHI (C-group), and GFK (intermediate group) of C. trachomatis (Washington Research Foundation, Seattle, WA) and Kajaani 6 strain of C. pneumoniae were used as antigens.…”
Section: Methodsmentioning
confidence: 99%
“…All three tests were performed according to the manufacturers' instructions. An in-house MIF assay was performed as described previously (9). Slides with antigens of C. trachomatis, C. psittaci, and C. pneumoniae (Labsystems OY) were used for this assay.…”
Section: Methodsmentioning
confidence: 99%